Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1073/pnas.2015331118
|View full text |Cite
|
Sign up to set email alerts
|

Ion mobility–mass spectrometry reveals the role of peripheral myelin protein dimers in peripheral neuropathy

Abstract: Peripheral myelin protein (PMP22) is an integral membrane protein that traffics inefficiently even in wild-type (WT) form, with only 20% of the WT protein reaching its final plasma membrane destination in myelinating Schwann cells. Misfolding of PMP22 has been identified as a key factor in multiple peripheral neuropathies, including Charcot-Marie-Tooth disease and Dejerine–Sottas syndrome. While biophysical analyses of disease-associated PMP22 mutants show altered protein stabilities, leading to reduced surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 82 publications
0
36
0
Order By: Relevance
“… The fact that proteins lacking basic residues favor the CRM over CEM reveals the limitations of using charge state signatures to assess the distribution of folded states . As a result, proteins with few ionizable groups may display diverging charging patterns upon unfolding. Previous studies have shown that point mutations can affect the CIU pattern of native-like protein ions by modulating their structure in solution. ,,, Our findings reveal that even identically folded proteins can exhibit different CIU fingerprints due to altered surface electrostatics during ESI. Because these differences arise from the locations of ESI charges, not from solution folding, care must be taken when using CIU data to probe solution structures. Gas-phase unfolding is routinely used to identify compounds that can stabilize protein complexes by occupying specific binding pockets. , We find that moving charged sites can have a dramatic effect on a protein’s conformation in the gas phase.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“… The fact that proteins lacking basic residues favor the CRM over CEM reveals the limitations of using charge state signatures to assess the distribution of folded states . As a result, proteins with few ionizable groups may display diverging charging patterns upon unfolding. Previous studies have shown that point mutations can affect the CIU pattern of native-like protein ions by modulating their structure in solution. ,,, Our findings reveal that even identically folded proteins can exhibit different CIU fingerprints due to altered surface electrostatics during ESI. Because these differences arise from the locations of ESI charges, not from solution folding, care must be taken when using CIU data to probe solution structures. Gas-phase unfolding is routinely used to identify compounds that can stabilize protein complexes by occupying specific binding pockets. , We find that moving charged sites can have a dramatic effect on a protein’s conformation in the gas phase.…”
Section: Discussionmentioning
confidence: 52%
“…(3) Previous studies have shown that point mutations can affect the CIU pattern of native-like protein ions by modulating their structure in solution. 9,15,54,55 Our findings reveal that even identically folded proteins can exhibit different CIU fingerprints due to altered surface electrostatics during ESI. Because these differences arise from the locations of ESI charges, not from solution folding, care must be taken when using CIU data to probe solution structures.…”
Section: ■ Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…IM separates the ions based on their size, shape, and charge. In native IM-MS experiments, we can separate different conformations and oligomeric states of membrane protein ions ( 55 , 56 , 57 , 58 , 59 ). All IM-MS data were collected using a Synapt G2 HDMS IM-Q-ToF mass spectrometer (Waters), with a direct infusion nESI source set to positive ion mode.…”
Section: Resultsmentioning
confidence: 99%
“…In native IM-MS experiments, we can separate different conformations and oligomeric states of membrane protein ions. (55)(56)(57)(58)(59) All IM-MS data were collected using a Synapt G2 HDMS IM-Q-ToF mass spectrometer (Waters, Milford, MA), with a direct infusion nESI source set to positive ion mode. Instrument settings were tuned to dissociate detergent micelles, with minimal perturbation of protein structure prior to the IM separator.…”
Section: Verteporfin Binds To C99 In Other Membrane Mimeticsmentioning
confidence: 99%